2013
DOI: 10.3892/br.2013.84
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclastogenesis accompanying early osteoblastic differentiation of BMSCs promoted by mechanical stretch

Abstract: Abstract. Mechanical stress plays a crucial role in bone formation and absorption. In previous studies, we verified the osteoblastogenesis of bone mesenchymal stem cells (BMSCs) affected by intermittent traction stretch. However, little is known about the osteoclastogenesis process under mechanical stimulation and its underlying association with osteoblastogenesis. In the present study, we investigated the osteoclastogenesis of BMSCs under this special mechanical stress. BMSCs were subjected to 10% elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, it is not unexpected that uniaxial cyclic stretch is believed to be of paramount importance in the development of functional musculoskeletal tissues [50] especially for the differentiation of MSCs into tendon/ligament fibroblasts. One aspect that needs to be considered is that the differences observed between our study and that of previous reports [5153] may have been related to the Flexcell system used in their studies. In contrast to the Strex machine used in our study, this device employs a suction mechanism at the centre of the elastomeric cell culture surface to create the stretching effect.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, it is not unexpected that uniaxial cyclic stretch is believed to be of paramount importance in the development of functional musculoskeletal tissues [50] especially for the differentiation of MSCs into tendon/ligament fibroblasts. One aspect that needs to be considered is that the differences observed between our study and that of previous reports [5153] may have been related to the Flexcell system used in their studies. In contrast to the Strex machine used in our study, this device employs a suction mechanism at the centre of the elastomeric cell culture surface to create the stretching effect.…”
Section: Discussionmentioning
confidence: 61%
“…It needs to be reminded however that these changes may be better applied for static cultures and probably not applicable to our stretching cultures [65, 66]. Results from other studies seem to suggest that this is the case [53, 67, 68]. Notwithstanding these limitations, the findings of the present study are still valid and useful owing to the robust study design employed.…”
Section: Discussionmentioning
confidence: 65%
“…The authors also found that this long term application of strain reduced the proliferative capacity of MSCs, supporting the notion that although short-term strains may increase proliferation, long-term strains do not appear to [7]. It has also been shown that both osteoblastogenesis and osteoclastogenesis are influenced by mechanical stimulation, showing how far reaching the effects of mechanical load are in bone formation and maintenance [30, 31]. …”
Section: The Effect Of Tensile Strain On Progenitor Cell Proliferatiomentioning
confidence: 68%
“…A series of signaling pathways, ion channels, and connections between the bone matrix and cytoskeleton were found involved in the cellular response to mechanical stress . Traditional cell culture stressing models include four-point bending stressing, FX-4000T , and FX-5000T, , but 2D culture and stressing methods cannot accurately simulate the 3D environment in which cells are placed in vivo, and it is questionable whether the reliability of the experimental results is representative of the stressing of cells in the 3D environment. In vivo, hJBMSCs are in a 3D mechanical microenvironment surrounded by an extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%